Ex ante impact evaluation of conditional cash transfer program on school attendance and poverty the case of the Philippines - Son, Hyun H.; Florentino, Jhiedon (The Philippine Review of Economics, 2009)
This paper provides an ex ante assessment of the implementation of the conditional cash transfer (CCT) program in the Philippines, called Pantawid Pamilyang Pilipino. This study investigates the impact of CCT on current poverty and that this extra money on school attendance under different transfer amounts and different targeting criteria such as universal targeting, geographical targeting, targeting of the poor, and progressive targeting.